Discourses of Decline Essays on Republicanism in Honor of Wyger R.E. Velema - Oddens, Joris (Studies in the History of Political Thought, 2021)
This volume explores the relevance of decline within the republican tradition. The essays in this volume focus on the Dutch Republic during the revolutionary era, as well as early modern Spain and Venice, the German Enlightenment, and the Weimar Republic. ; Readership: Students of republicanism, political culture, intellectual history, the history of political thought, the Age of Enlightenment and Revolutions, the history of the Netherlands, early modern European history, and German history.